BUREAU INTERNATIONAL DES EXPOSITIONS - Expositions et Transformations Urbaines / Expo Cities - Urban Change - Vila Vázquez, José Ignacio (ZARCH, 2019)
Bureau international des expositions Expositions et Transformations Urbaines / Expo Cities- Urban Change. Bulletin 2018 Bureau international des expositions ISBN: 978-2-9558188-2-4